Congenital vascular hamartoma in the spinal cord of a neonatal foal - Paz, Tatiana; Henderson, Eileen; Asín, Javier; Streitenberger, Nicolas; Uzal, Francisco A. (Brazilian Journal of Veterinary Pathology, 2025)
A three-day-old Arabian filly with a history of not being able to stand unassisted after birth and lack of control overthe right front and right hind limbs. The filly had inadequate proprioceptive responses, with absent pain/withdraw answer, andfailed to respond to medical therapy. Due to the poor prognosis, euthanasia was elected, and a full necropsy was performed.